Review of Teachers Professional Development Research Studies in South East Asia - Widiarto Adhi Setiawan; Paulus Kuswandono (International Journal of Pedagogy and Teacher Education, 2020)
This article discusses and reviews English teacher professional development (TPD) research studies carried out in South East Asia between 2010 and 2018. There is a need to review previous English TPD because new teaching methods are required to develop 21st-century students’ competencies due to the aim of changing the focus of English learning in school from grammar to conversational English and the use of computers in the classroom. This study aims to find the focus and types of English TPD trends in South East Asia to improve our understanding of what contributes to the effectiveness of the TPD programmes, which, in turn, may facilitate successful implementation of innovations in English language education. The researchers used the ERIC, Scopus and Google Scholar search engines to find English TPD research papers in South East Asia. The reviewed studies were conducted in Singapore, Indonesia, Malaysia, Thailand and Vietnam. The researchers performed the analysis by reviewing the studies and coding them for themes and notions using the frame based on the checklist proposed by Hunzicker (2011), namely supportive, job-embedded, instructional focus and ongoing components for TPD analysis. These reviewed studies appeared to be focused on observation research and action research.